2015
DOI: 10.1063/1.4921887
|View full text |Cite
|
Sign up to set email alerts
|

Microwave holography using a magnetic tunnel junction based spintronic microwave sensor

Abstract: In this work, a spintronic sensor based microwave holographic imaging system is developed, demonstrating the feasibility of microwave holographic imaging applications using a spintronic microwave sensor. The high sensitivity of the microwave phase measurement allows the coherent imaging of the target reconstructed in noise environments. Adapting the broadband measurement, not only the shape but also the distance of target can be determined, which implies that a three-dimensional imaging is achievable using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This provides a promising approach for microwave imaging, which can be potentially applied in biomedical devices. Moreover, in the work by Fu et al., [ 77 ] an STD‐based RF holographic imaging system was developed, demonstrating the feasibility of RF holographic imaging applications using STD. It was demonstrated that high sensitivity of the RF phase measurement leads to the coherent reconstructed target imaging in noise environments.…”
Section: Std's Applicationsmentioning
confidence: 99%
“…This provides a promising approach for microwave imaging, which can be potentially applied in biomedical devices. Moreover, in the work by Fu et al., [ 77 ] an STD‐based RF holographic imaging system was developed, demonstrating the feasibility of RF holographic imaging applications using STD. It was demonstrated that high sensitivity of the RF phase measurement leads to the coherent reconstructed target imaging in noise environments.…”
Section: Std's Applicationsmentioning
confidence: 99%
“…In this work, we study the potential of the method of holographic detection and visualization of objects using highly sensitive spin diodes. Those diodes possess advantages at low microwave irradiation power [3][4][5][6][20][21][22] and can show a significantly higher sensitivity than the sensitivity of a Schottky diode at a similar level of equivalent input noise [16]. Estimates show that for a specified sensitivity, taking into account the radiation safety standards, there exists at least 25 m safe obstacle detection range.…”
Section: Introductionmentioning
confidence: 99%
“…, where in P is the input microwave power, can exceed the sensitivity of a semiconductor Schottky diode by an order of value in the presence of the bias current [2][3][4]. High effect of the rectification of the microwave signal in MTJ makes spintorque diode attractive for practical applications in the microwave vision techniques [5]. However, the threshold current density, in the vicinity of which there is a sharp increase in the spin-torque diode sensitivity, is generally high.…”
Section: Introductionmentioning
confidence: 99%